Evaluation of circulating tumor DNA as a prognostic and predictive biomarker in BRAF V600E mutated colorectal cancer—results from the FIRE‐4.5 study - Susanne Klein‐Scory; Alexander Baraniskin; Wolff Schmiegel; Thomas Mika; Roland Schroers; Swantje Held; Kathrin Heinrich; David Tougeron; Dominik P. Modest; Ingo Schwaner; Jan Eucker; Rudolf Pihusch; et al. (Molecular Oncology)
The randomized FIRE‐4.5 (AIO KRK0116) trial compared first‐line therapy with FOLFOXIRI (folinic acid, fluorouracil, oxaliplatin, and irinotecan) plus either cetuximab or bevacizumab in B‐Raf proto‐oncogene, serine/threonine kinase (BRAF) V600E‐mutant metastatic colorectal cancer (mCRC) patients. This study was accompanied by a prospective translational project analyzing cell‐free circulating tumor DNA (ctDNA) in plasma to test whether ctDNA analysis may help to guide clinical treatment decision making. FIRE‐4.5 included mCRC patients with BRAF V600E mutation detected by tissue‐based analyses. Liquid biopsies (LBs) were collected at baseline (pre‐treatment) and during therapy. Digital droplet PCR (ddPCR) technology was applied for determination of BRAF mutations and the in vitro diagnostics (IVD)‐certified ONCOBEAM RAS procedure for analysis of RAS mutations. The BRAF V600E variants in ctDNA were analyzable in 66 patients at start of the therapy, at baseline. No BRAF V600E mutations were detected in 26% (17/66) of patients and was associated with a significantly longer progression‐free survival (PFS: 13.2 vs 6.5 months; HR 0.47; P = 0.014) and overall survival (OS: 36.8 vs 13.2 months; HR 0.35; P = 0.02) as compared to ctDNA mutant patients. Patients with detectable BRAF mutations showed a clear superiority of FOLFOXIRI plus bevacizumab with regard to PFS (10.4 vs 5.7 months; HR 0.4; P = 0.009) and OS (16.6 vs 11.6 months; HR 0.5; P = 0.15), while this was not the case for BRAF wild‐type patients. Follow‐up LBs were obtained from 51 patients. Patients converting from BRAF V600E mutant to a BRAF V600 wild‐type status (36%, N = 18) had a superior PFS (8.6 vs 2.3 months; P = 0.0002) and OS (17.4 vs 5.1 months; P < 0.0001) compared to patients with stable or increased mutational allele frequency (12%, N = 6). Those patients also achieved a significantly greater disease control rate (89% vs 20%; P = 0.008). In conclusion, LB evaluating ctDNA is informative and may help to guide treatment in patients with BRAF V600E‐mutated mCRC.